2022
DOI: 10.1007/s00167-022-07096-y
|View full text |Cite
|
Sign up to set email alerts
|

Explosive hamstrings strength asymmetry persists despite maximal hamstring strength recovery following anterior cruciate ligament reconstruction using hamstring tendon autografts

Abstract: Purpose To investigate the differences in maximal (isometric and concentric peak torque) and explosive (rate of torque development (RTD)) hamstring and quadriceps strength symmetry between males and females during early- and late-phase rehabilitation after anterior cruciate ligament reconstruction (ACLR) using hamstring tendon (HT) autografts and to determine the interaction of time and sex on maximal and explosive strength symmetry. Methods A total of 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Future work in the female population is still needed given the previously reported differences in lower limb strength and biomechanics between the sexes. 40 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Future work in the female population is still needed given the previously reported differences in lower limb strength and biomechanics between the sexes. 40 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Similar data, with no difference in extensor strength but decreased flexor strength when using HT, is also reported when comparing BPTB and HT [ 6 , 42 , 67 ]. Interestingly, a recent study showed that maximal hamstring strength, but not explosive hamstring strength improved over time following ACL-R using HT [ 114 ]. Comparing QT to BPTB, similar levels of quadriceps recovery have been observed in the short term [ 39 , 51 ].…”
Section: Introductionmentioning
confidence: 99%